Stent Grafts Can Convert Unusable Upper Arm Arteriovenous Fistulas into a Functioning Hemodialysis Access: A Retrospective Case Series - Bavare, Charudatta S.; Street, Tiffany K.; Peden, Eric K.; Davies, Mark G.; Naoum, Joseph J. (Frontiers in Surgery, 2017)
Introduction Not all newly created arteriovenous fistulas (AVFs) successfully mature and develop into a functioning access for hemodialysis. Percutaneous transluminal angioplasty (PTA) and balloon-assisted maturation (BAM) have been utilized to either treat flow-limiting stenoses or to promote and accelerate maturation. We hypothesized that unusable upper arm AVFs can be rescued by conversion to a functional access using the percutaneous placement of a stent graft (SG). Methods Clinical data on 12 patients with an early non-usable upper arm AVF underwent percutaneous revision using SGs. There were six brachial–cephalic, three brachial–basilic, and three brachial–brachial vein transposition AVFs. Results All patients had either at least two or more stenoses (>2 cm) within the fistula conduit, or a long segment stenosis (>4 cm) in combination with shorter segment stenoses. Nine patients had failed PTA. Three patients had failed BAM at outside access centers. All patients were referred for failure to achieve access cannulation and concomitant hemodialysis through the AVF. SGs were placed retrograde toward the arterial anastomoses and ranged in diameter (6, 7, and 8 mm in four, seven, and one patients, respectively). The average length of the SG was 10 cm (range 5–15 cm). All SGs were post-balloon dilated at the time of placement. All AVFs were salvaged, and patients were able to maintain functional use of their access with cannulation occurring through the SG. The primary patency rate at 6 and 12 months was 91% [95% confidence interval (CI), 56–98%] and 65% (95% CI, 32–87%), respectively (n = 11 and 5 at risk, respectively). The secondary patency rate at 6 and 12 months was 100 and 72% (95% CI, 46–93%), respectively (n = 11 and 7 at risk, respectively). Conclusion This report outlines a successful initial experience using SGs to rescue, preserve, and convert an unusable upper arm AVF into a functioning hemodialysis access.